Unlocking the epigenetic code: new insights into triple-negative breast cancer - Mahendran, Gowthami; Shangaradas, Ann Dharshika; Romero-Moreno, Ricardo; Wickramarachchige Dona, Nadeeshika; Sarasija, S. H. G. Sumudu; Perera, Sumeth; Silva, Gayathri N. (Frontiers in Oncology, 2024)
Triple-negative breast cancer (TNBC) is a highly aggressive and clinically challenging subtype of breast cancer, lacking the expression of estrogen receptor (ER), progesterone receptor (PR), and HER2/neu. The absence of these receptors limits therapeutic options necessitating the exploration of novel treatment strategies. Epigenetic modifications, which include DNA methylation, histone modifications, and microRNA (miRNA) regulation, play a pivotal role in TNBC pathogenesis and represent promising therapeutic targets. This review delves into the therapeutic potential of epigenetic interventions in TNBC, with a focus on DNA methylation, histone modifications, and miRNA therapeutics. We examine the role of DNA methylation in gene silencing within TNBC and the development of DNA methylation inhibitors designed to reactivate silenced tumor suppressor genes. Histone modifications, through histone deacetylation and acetylation in particular, are critical in regulating gene expression. We explore the efficacy of histone deacetylase inhibitors (HDACi), which have shown promise in reversing aberrant histone deacetylation patterns, thereby restoring normal gene function, and suppressing tumor growth. Furthermore, the review highlights the dual role of miRNAs in TNBC as both oncogenes and tumor suppressors and discusses the therapeutic potential of miRNA mimics and inhibitors in modulating these regulatory molecules to inhibit cancer progression. By integrating these epigenetic therapies, we propose a multifaceted approach to target the underlying epigenetic mechanisms that drive TNBC progression. The synergistic use of DNA methylation inhibitors, HDACi, and the miRNA-based therapies offers a promising avenue for personalized treatment strategies, aiming to enhance the clinical outcome for patients with TNBC.